Happy Victimizing in Emerging Adulthood - Eveline Gutzwiller-Helfenfinger; Brigitte Latzko (Frontline Learning Research, 2020)
This study contributes to a developmental approach focusing on emotions as being of key significance in explaining the Happy Victimizer pattern (HV pattern) among adults. Based on findings from our own research on moral emotions within the Happy Victimizer paradigm, we claim that a purely cognitive approach to explain the HV is overly narrow. Instead, we argue that emotion attributions serve as a source for moral motivation. By identifying new dimensions (i.e., deontic judgment; own action choice; self-constructed emotion attributions) to explain the complexity of moral functioning in emerging adulthood, the current study contributes to a theoretical and methodological framework that integrates both cognitive and emotional processes to bridge the gap between moral thought, emotion, and action with the aim of fostering moral learning across the lifespan.